A stochastic mudharabah model for investment in bursa Malaysia syariah counters / Aslina Omar - Omar, Aslina (2013)
In Islam, all decisions, activities, policies, strategy and interaction in the economy do not end with the profit or loss only, but are directly related to human relationships. This is also believed in other religions. Hence in the Islamic financial System, the syariah rules are considered in all economic activities including investment. Investment is money or capital commitment for the purchase of financial instruments or other assets to recover the benefits in the form of interest income. Most of the investment opportunities offered are interest based but Islamic law strictly prohibits interest or usury, also commonly called riba in Arabic. The prohibition of riba has led to the creation of alternatives schemes for the compensation of investment capital. One of the methods of compensation is by means of profit-sharing and one of the financial contracts that internalize profit sharing is mudharabah. It is an investment partnership in which one party called rab ul mal provides capital while the other party called mudharib brings labor and effort with the provision of profit sharing in some pre-determined proportions. This study derives the new mudharabah investment model by using the stochastic calculus. This model can be used in stock market investment. Based on the results it shows that the new mudharabah investment model is useful in investing in stock market since it has the accurate forecasting stock prices and profit rate.